2018
DOI: 10.1111/1742-6723.12977
|View full text |Cite
|
Sign up to set email alerts
|

oneED: Embedding a mindfulness‐based wellness programme into an emergency department

Abstract: A departmental wellness programme embedding mindfulness practice is feasible and sustainable. Potential for success is enhanced by an approach that is open to modification according to each institution's culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The introduction of mindfulness in emergency departments is feasible and may improve the well-being of healthcare professionals working in stressful conditions [ 24 , 25 ]. Focusing on the present moment can help both young doctors and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of mindfulness in emergency departments is feasible and may improve the well-being of healthcare professionals working in stressful conditions [ 24 , 25 ]. Focusing on the present moment can help both young doctors and their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Improving mindfulness is worth considering since it is a modifiable characteristic and can lead to better patient care. It seems that the implementation of mindfulness training in emergency medicine departments is feasible and sustainable [30]. After completing mindfulness courses, residents have admitted increased awareness, self-reflection, self-acceptance at work, and acceptance of their own limitations [31].…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of this study revealed a high percentage of participant adherence to the program and decreased stress scores from baseline to after the program (Gauthier et al, 2015). Braganza, Young, Sweeny, and Brazil (2018) implemented short, 4-minute pauses at the beginning of ED shifts, as well as 30-minute drop in sessions. The program resulted in participants' increased knowledge of mindfulness and increased frequency of practicing mindfulness (Braganza et al, 2018).…”
Section: Terminologymentioning
confidence: 94%
“…Braganza, Young, Sweeny, and Brazil (2018) implemented short, 4-minute pauses at the beginning of ED shifts, as well as 30-minute drop in sessions. The program resulted in participants' increased knowledge of mindfulness and increased frequency of practicing mindfulness (Braganza et al, 2018). Several studies have successfully implemented mindfulness programs with interprofessional groups, demonstrating that the involvement of a variety of health-care professionals in mindfulness practice is both necessary and useful (Goodman & Schorling, 2012;Mackenzie, Poulin, & Seidman-Carlson, 2006;Shapiro, Astin, Bishop, & Cordova, 2005).…”
Section: Terminologymentioning
confidence: 99%